Entrevista: Eder Pires de Camargo y Jairo Gonçalves Carlos - Castiblanco, Olga; Pires de Camargo, Eder; Gonçalves Carlos, Jairo (Góndola, Enseñanza y Aprendizaje de las Ciencias, 2014)
Ver documento completo en pdf.